Effect of Nitrogen and Phosphorus Levels on Yield, Concentration, Physical and Chemical Properties of Dill Seed Oil - H Al-Sahaf, Fadhil; H Al-Samara’i, Madeha; J Al-Ndawi, Muna (Iraqi Journal of Pharmaceutical Sciences, 2017)
To test the effect of 4 levels of nitrogen (i.e. 0, 45, 90 and 135 Kg N ha-1) as urea (46% N) and 3 levels of phosphorus (i.e. 0, 17.5 and 35 Kg P ha-1) as triple superphosphate (21.8% P) on yield and concentration of dill (Anethum graveolens L. local cultivar) seed oil this experiment was carried out during winter season of 1999 - 2000 at the experimental field of Agriculture College, Abu-Ghraib. Both fertilizers were applied in two equal splits, first at seeds sowing and the second was added one month after emergence. Dried and ground seed samples were subjected to water distillation for extraction of volatile oils Result indicated that fertilization of dill plants with 90 Kg N + 35 Kg P ha-1 produced highest oil yield (32.19ha-1) and concentration (3.60%) with better quality. GLC analysis indicated that dill seed oil contain 27 volatile compounds, 15 were identified and the major constituents were Carvone, Limonene and α-Phellandrene. Nitrogen and phosphorus fertilization increased the concentration of all identified constituents of dill seed oil. Nitrogen and phosphorus fertilization increased yield and concentration of dill seed oil. Moreover, physical properties of the oil were also improved by N and P fertilization. GLC analysis showed that Carvone, Limonene and α-Phellandrene are the major constituents of dill seed oil and could be increased by N and P application .Key words : Volatile compounds, Carvone, Limonene, α-Phellandrene.